Platelet count estimation: a prognostic index in pregnancy induced hypertension - Gupta, Aakriti; Hak, Jyoti; Sunil, Isha; Gupta, Amita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertension in pregnancy is one of the serious complications of pregnancy with an incidence of 5% to 7% of all pregnancies, particularly in cases with preeclampsia and eclampsia. Though platelet count during pregnancy is within the normal non pregnant reference values, there is a tendency for the platelet count to fall in late pregnancy. The frequency and intensity of maternal thrombocytopenia varies and is dependent on the intensity of the disease process and duration of PIH syndrome. Methods: A prospective observational study was conducted on 200 pregnant women attending OPD Or Inpatients in the Department of Obstetrics and Gynecology, SMGS Hospital, GMC Jammu from November 2015 to October 2016. Pregnant women beyond 28 weeks gestation of pregnancy are included and divided into two groups i.e. the study and control group. Platelet counts will be done every 4 weeks in controls and weekly in subjects from 28 weeks till delivery. Results: The mean platelet count observed among cases of mild preecclampsia, severe preeclampsia and ecclampsia was 2.26, 1.63 and 0.99 lakh/mm3 respectively. The difference in mean platelet count among cases and controls was statistically significant. The association of platelet count with severity of different categories of PIH was analysed statistically and was highly significant. Conclusions: Platelet count is a very important investigation for the antenatal mother having PIH, as it is directly related to maternal and perinatal outcome. Routine and regular monitoring of platelet count can be included in the routine antenatal checkup among the pregnant women with PIH.